Factors influencing intention of Muslim consumer to purchase Halal cosmetic product / Ain Syuhadah Mohd Sait - Mohd Sait, Ain Syuhadah (Faculty of Business and Management, 2019)
The purpose of the research is to examine the factor that influencing the intention of Muslim consumers to purchase the halal cosmetic product in Gombak, Selangor that might be one of the most significant variables of Shariah law. One of the aims of this study is to expose factors that can influence the purchase intention. This study attempts to observe the factors that influence the relationship between the factors which are halal awareness, halal knowledge, religious beliefs, and halal certification and purchase intention towards halal cosmetic products. Primary data was collected through questionnaire by distributing to the consumers which stayed at Gombak, Selangor. Data analysis was completed using the statistical package for social science (SPSS). The analysis was done to achieve objectives of this study which are to identify the level of purchase intention on halal cosmetic products, to identify the significant relationship between halal awareness, halal knowledge, religious belief and halal certification with purchase intention and to identify the most influential factor towards purchase intention. Based on research findings, all variable (halal awareness, halal knowledge, religious belief, and halal certification) are positively significant with purchase intention. Lastly, the researcher hopes that this study will help the manufacturers know the important factors influencing consumers purchase intention toward halal cosmetics.